Renal Protective and Lipid Profile Modulatory Effects of Ethanol Extract of Anthocleista vogelii Stem Bark (EASB) in Renal Injury Rats Induced with Carbon-tetrachloride (CCl4) - Robert Ikechukwu Uroko; Nnanna Charles Chukwu; Paul Chukwuemaka Nweje-anyalowu; Chinonso Friday Aaron (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
The study evaluated the effects of ethanol extract of Anthocleista vogelii stem bark (EASB) on renal function indices and lipid profile in rats induced renal injury with CCl4. Following a completely randomized experimental design, 30 rats were randomly distributed into 6 groups (n = 5). Group 1 was the normal control, group 2 was the negative control while group 3 was the silymarin control. Groups 4 – 6 were CCl4 induced but treated with 100, 200, and 400 mg/kg EASB/day respectively. The study was conducted using appropriate methods. The results showed that the negative control had a significant (P<0.05) increase in the serum urea, creatinine, cholesterol, triacylglycerol (TAG), low-density lipoprotein (LDL) concentrations, and a significant reduction in the serum high-density lipoprotein (HDL) concentration relative to the normal control. Treatments with EASB lowered the serum creatinine, urea, and TAG concentrations when compared with the negative and silymarin controls respectively. The EASB at 100 mg/kg restored the serum HDL concentration to a normal level but 200 and 400 mg/kg EASB/day caused no significant (P>0.05) increase in the serum HDL concentrations relative to the negative control. The rats treated with EASB had elevated serum LDL and cholesterol concentrations in comparison with the negative and silymarin controls. Treatments with EASB prevented the tubular necrosis, degeneration, and infiltration of inflammatory leucocytes observed in the kidney histomorphology of the negative control. These findings suggest that EASB improves renal function and some lipid profile parameters but could cause dyslipidemia when taken in excess dose.